Lietuvių kalbos būdvardžių būtinojo semantinio valentingumo raiška - Tekorienė, Dalija (Kalbotyra, 1985)
On the semantic level it has been established that in Modern Lithuanian there are about 70 bivalent adjectives which possess two obligatory semantic actants – the possessor of the property and the complement. On the surface level both actants must have some kind of explicit or implicit expression, otherwise the meaning of the adjective is not fully realized. The paper describes various ways in which the complementary actant of the Lithuanian adjective can be signalled on the surface level, and draws several conclusions concerning the relationship between semantic and syntactic valency. Although each adjective has its own selection of the peculiar ways in which its complementary actant may be expressed, all the bivalent adjectives can have their complementary actant expressed by a word form or a phrase directly dependent on the adjective. Such word forms are called syntactic actants. If this is the only way in which the complementary actant of an adjective can be expressed, the syntactic valency of the adjective is obligatory. If the syntactic actant of an adjective is only one of the several possible ways of expressing the complementary actant, the syntactic valency of the adjective is optional.